2013
DOI: 10.1016/j.trac.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Analytical challenges in breath analysis and its application to exposure monitoring

Abstract: There is an increasing interest in the use of breath analysis for monitoring human physiology and exposure to toxic substances or environmental pollutants.This review focuses on the current status of the sampling procedures, collection devices and sample-enrichment methodologies used for exhaled breath-vapor analysis. We discuss the different parameters affecting each of the above steps, taking into account the requirements for breath analysis in exposure assessments and the need to analyze target compounds at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 123 publications
(308 reference statements)
1
40
0
Order By: Relevance
“…As many factors, including the exposure concentrations and durations, physiological and metabolic differences of individuals, types of breath samples (mixed exhaled air or alveolar air), sampling and analytical methods [27,[101][102][103], could affect the respiratory AFs, it is difficult to determine whether the differences in AFs between studies were due to differences in subjects, test methods or exposure concentrations (much lower in this study than in the previous studies). However, the AFs observed in this study under low-level BTEX exposure were comparable with most of those conducted under unbelievably high BTEX exposure concentrations, suggesting that initial exposure concentration might not be a critical factor to the AFs considering that the possible errors might also be brought by variability in individual subjects and test methods.…”
Section: Preliminary Tests Of Real-time Afsmentioning
confidence: 79%
See 1 more Smart Citation
“…As many factors, including the exposure concentrations and durations, physiological and metabolic differences of individuals, types of breath samples (mixed exhaled air or alveolar air), sampling and analytical methods [27,[101][102][103], could affect the respiratory AFs, it is difficult to determine whether the differences in AFs between studies were due to differences in subjects, test methods or exposure concentrations (much lower in this study than in the previous studies). However, the AFs observed in this study under low-level BTEX exposure were comparable with most of those conducted under unbelievably high BTEX exposure concentrations, suggesting that initial exposure concentration might not be a critical factor to the AFs considering that the possible errors might also be brought by variability in individual subjects and test methods.…”
Section: Preliminary Tests Of Real-time Afsmentioning
confidence: 79%
“…Nowadays, human breath analysis has become an emerging bio-monitoring tool frequently used in clinical disease diagnosis for endogenous VOCs and exposure risk assessment for exogenous VOCs [27]. Compared to blood or urine analysis, breath analysis has many advantages, such as noninvasive, easily repeated, totally painless and agreeable to subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-naïve lung cancer patients were chosen to participate in our study to ensure that drug treatment would not affect the accuracy of the result and secondly, to study the performance of the sensor in diagnosing suspected lung cancer before diagnostic and treatment intervention. For breath analysis, the exhaled breath was not sampled or stored in collection bags for later analysis, instead, the levels of exhaled alkane compounds were measured on-site directly and immediately so the decomposition or the loss of VOCs by diffusion would not take place (30,31). Study subjects exhale 200 times to ensure sufficient period of time for the sensor to reach peak resistance, as our preclinical experiments showed that it could take up to 500 s to generate sensor peak output.…”
Section: Discussionmentioning
confidence: 99%
“…Tidal breathing, which was the breathing manoeuvre used in this study, was considered the most reliable methodology (31). The study subjects participating in our study were encouraged to ventilate normally and naturally in the study, and breath samples were obtained from a series exhalation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exhaled breath analysis can be done rapidly with fast turnaround time and minimal biohazard waste [11]. However, VOCs differ in their physico-chemical characteristics, and thus pose sampling and analytical challenges for routine breath analysis at a wide network of monitoring sites where outdoor/indoor or occupational exposures are of concern [12].…”
Section: Introductionmentioning
confidence: 99%